Analytical and experimental investigation on elastic modulus of reinforced additive manufactured structure. (5th February 2015) - Sugavaneswaran, M.; Arumaikkannu, G.
Highlights: Novel and cost effective method for fabrication of multi material structure in additive manufacturing technique. Improvement in elastic modulus was 6.7–21.9% in multi materials structure and its fracture surface analysis was studied. Additive manufactured structure stiffness can be customized by means of reinforcement stacking sequence. Mechanics of composite materials was proposed to determine the property of additive manufactured multi material structure. Theoretical and experimental method showed a high correlation with error levels below 10%. Abstract: Additive Manufacturing (AM) technique has been utilized in a variety of engineering applications because of its desirable characteristic of mass customized manufacturing. Polyjet 3 Dimensional Printing (3DP) is one among the various AM techniques which is well known for fabrication of part with multiple materials. Meanwhile, strength and stiffness of polyjet 3DP part is typically less and hence it is difficult to use it for engineering applications. To maximize polyjet 3D printed part stiffness, this study explores the novel methodology by incorporating high strength material among the multi materials as reinforcement in Additive Manufactured Multi Material (AM MM) structure. Uni-axial tensile test and fracture surface analysis over reinforced AM structure was carried out to investigate the influence of reinforcement and its orientation with respect to loading direction. The experimental result shows that addition of reinforcement enhanced the elastic modulus significantly as well as improvement in elastic modulus varies between 6.79% and 21.03% with respect to reinforcement orientation. Along with this, we have proposed simpler analytical method based upon Rule of Mixture (RoM) equation to predict the elastic modulus of reinforced AM structure. Comparison of the analytical method results with the experimental results implies that there is a good agreement between them. Methodology proposed in this work could be very useful in the cases of predicting strength of reinforced AM structure for engineering application.